Review of non-contact methods for automated aircraft inspections - Lafiosca, Pasquale; Fan, Ip-Shing (British Institute of Non-destructive Testing, 2020)
Damage on the aircraft structure can be caused by lightning strikes, hail, accidental impacts or ageing. Scratches or dents on the aircraft surface are typical indications of impact damage. General visual inspection (GVI) is the primary way in which to detect such forms of damage. The inspection process is time consuming, raises safety concerns for the inspector and is subject to variations due to human factors. Significant inspection automation remains challenging, mainly because GVI requires the critical human ability to assess anomalies. Also, damage specifications in maintenance manuals are influenced by human interpretation. Some automated tools are beginning to be available for aircraft inspection checks. However, none of them are capable of replacing the inspector judgement yet. Humans still need to manually assess the location or the data generated by the tools. Their performance is also affected by different environmental conditions, materials and the overall characteristics of the damage. This review presents the main methods for non-contact visual aircraft inspection, explaining their basic working principles and limitations. Their suitability for automation in aircraft inspection is also discussed
Keywords: Triangulation; Time-of-flight; Thermography; Aircraft Inspection; Stereo vision; Structured light; Pattern Recognition